Объяснение:
найдем длины всех отрезков
[tex]kl = \sqrt{ {(3 - ( - 2))}^{2} + {( - 3 - 8)}^{2} } = \sqrt{ {5}^{2} + {( - 11)}^{2} } = \sqrt{25 + 121} = \sqrt{146} [/tex]
[tex]lm = \sqrt{ {(6 - 3)}^{2} + {(2 - ( - 3))}^{2} } = \sqrt{ {3}^{2} + {5}^{2} } = \sqrt{9 + 25} = \sqrt{34} [/tex]
[tex]mn = \sqrt{ {(1 - 6)}^{2} + {(13 - 2)}^{2} } = \sqrt{ {( - 5)}^{2} + {11}^{2} } = \sqrt{25 + 121} = \sqrt{146} [/tex]
[tex]kn = \sqrt{ {(1 - ( - 2))}^{2} + {(13 - 8)}^{2} } = \sqrt{ {3}^{2} + {5}^{2} } = \sqrt{9 + 25} = \sqrt{34} [/tex]
так как KL=MN и LM=KN тогда KLMN - паралелограм
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
найдем длины всех отрезков
[tex]kl = \sqrt{ {(3 - ( - 2))}^{2} + {( - 3 - 8)}^{2} } = \sqrt{ {5}^{2} + {( - 11)}^{2} } = \sqrt{25 + 121} = \sqrt{146} [/tex]
[tex]lm = \sqrt{ {(6 - 3)}^{2} + {(2 - ( - 3))}^{2} } = \sqrt{ {3}^{2} + {5}^{2} } = \sqrt{9 + 25} = \sqrt{34} [/tex]
[tex]mn = \sqrt{ {(1 - 6)}^{2} + {(13 - 2)}^{2} } = \sqrt{ {( - 5)}^{2} + {11}^{2} } = \sqrt{25 + 121} = \sqrt{146} [/tex]
[tex]kn = \sqrt{ {(1 - ( - 2))}^{2} + {(13 - 8)}^{2} } = \sqrt{ {3}^{2} + {5}^{2} } = \sqrt{9 + 25} = \sqrt{34} [/tex]
так как KL=MN и LM=KN тогда KLMN - паралелограм